Biochar and Sewage Sludge Application Increases Yield and Micronutrient Uptake in Rice (Oryza sativa L.). Issue 13 (20th July 2018) - Jatav, Hanuman Singh; Singh, Satish Kumar; Singh, Yadvir; Kumar, Omkar
ABSTRACT: A greenhouse experiment was conducted in the Department of Soil Science and Agricultural Chemistry, Institute of Agricultural Sciences, Banaras Hindu University, Varanasi (U.P.), India, during kharif 2013 to find out the effect of biochar and sewage sludge (SS) on growth, yield, and micronutrient uptake in rice crop. Nine treatments were employed using six different doses of biochar (2.5, 5.0, 7.5 10, 15, and 20 t ha −1 ) amended with a fixed dose of SS (30 t ha −1 ) and 50% recommended dose of nitrogen (50% RDN), i.e., 60 kg ha −1 . Other three treatments were absolute control (no fertilizers), 100% recommended dose of fertilizers (100% RDF) which was 120:60:60 kg ha −1 as nitrogen (N): phosphorus pentoxide (P2 O5 ):dipotassium oxide (K2 O), and 30 t ha −1 SS + 50% RDN. Experimental results showed a significant increase in yield of rice crop with increasing levels of biochar along with SS. Application of biochar at 20 t ha −1 along with 30 t ha −1 SS increased grain yield to the extent of 2.5 times over absolute control (no fertilizers) and 8.5% over control (100% RDF). The uptake of iron (Fe), copper (Cu), zinc (Zn), and manganese (Mn) (micronutrients) increased significantly with graded doses of biochar application from 2.5 to 20 t ha −1 in the soil. The maximum micronutrient uptake and grain yield of rice were found in T9 where 30 t ha −1 SS along with 20 t ha −1 biochar was applied with only 50% RDN. The maximum availability of micronutrients in soil was found with 30 t ha −1 of SS + 50% RDN (T3 ) followed by conjoint application of 20 t ha −1 of biochar and 30 t ha −1 SS + 50% RDN (T9 ).